Value of baseline and end of chemotherapy 18F-FDG PET/CT in pediatric patients with Burkitt lymphoma. Issue 12 (15th October 2021) - Xiao, Zizheng; Mo, Yiwen; Long, Wen; Li, Ruping; Li, Xinling; Wei, Yuan; Fan, Wei; Zhang, Xu
Abstract: The aim of this study was to analyze whether the baseline metabolic parameters of 18 F-FDG PET/CT in pediatric patients with Burkitt lymphoma (BL) can predict treatment response and prognosis. We retrospectively analyzed 68 pediatric patients with BL who underwent PET/CT before treatment. PET images were analyzed semi-quantitatively by measuring the maximum standardized uptake (SUVmax), total metabolic tumor volume (tMTV), and total lesion glycolysis (TLG). Survival curves were plotted according to the Kaplan–Meier method. Univariate and multivariate Cox proportional hazards regression models were used to assess the relation between potential variables and outcomes. tMTV and TLG were significantly lower in patients with complete response compared with those with partial response at the end of treatment. PET metabolic parameters (tMTV and TLG) were the independent prognostic values for outcome. TMTV and TLG were significantly connected with treatment response and prognosis in pediatric with BL.